Actual Problems of Banking Regulation in Kazakhstan - SADVOKASSOVA, Kulyash Zh.; KODASHEVA, Gaukhar S.; KHAMITKHAN, Nazgul; ZHAMIYEVA, Aizhan Ye.; SADVOKASSOV, Rustem K. (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The article discusses the current problems of banking regulation in Kazakhstan in the face of growing uncertainty in the financial market. In this context, an assessment of the current practice of banking regulation has been given, the strengths and weaknesses of this process have been identified, as well as problems with the introduction of Basel III international banking supervision standards and ways to further improve the national banking regulation system in modern conditions. All these questions considered in this article determine the relevance of the presented material. The materials of the article suggest practical significance for university professors of economic specialties.